Intervensi Sosial bagi Anak Korban Kekerasan Seksual di Sentra “Handayani” Jakarta Timur - Amalia Diah Kusumawardhani; Muhammad Sahrul (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aims to analyze the stages, impacts, and supporting and inhibiting factors of social intervention for child victims of sexual violence at the “Handayani” Center, East Jakarta. This research employs a qualitative descriptive approach to obtain an in-depth understanding of the intervention process. Data were collected through observation, in-depth interviews, and documentation, and analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The results indicate that the “Handayani” Center applies the Generalist Intervention Model (GIM) through seven stages: engagement, assessment, planning, implementation, evaluation, termination, and follow-up. The social intervention has a positive impact on children, particularly in improving emotional stability, self-confidence, and social functioning. Furthermore, the intervention supports children’s readiness for social reintegration. Supporting factors include the professionalism of social workers and effective team collaboration, while inhibiting factors consist of high workload, delays in administrative reporting, and limited family support.